Posthumanity in DeLillo’s Zero K: the rising connections between identity and technology - Alan Medeiros Casteluber; Giséle Manganelli Fernandes (Ilha do Desterro)
In Zero K, DeLillo revisits the ever-increasing connection between identity and technology However, he does so in a unique way, adding (im)mortality issues to an already complex mix. As a result, DeLillo not only explores the intricacies of our present context, but also provides a bleak picture of what could be our posthuman future. This paper examines how DeLillo’s fiction reveals subjectivity in our current post-modern society. The focus of this investigation gravitates specifically to the interference of a technological influx that overtakes contemporary life. It analyzes the process by which our interdependence in machines, electronic devices, and its systems has made them an extension of our own body. Pushing the boundaries of this relationship to an extreme, the book explores the distorted view of technology as “another God”, but, unlike the other gods, it actually "delivers” salvation.